Correction: Spectroscopic characteristics of the OSIRIS near-backscattering crystal analyser spectrometer on the ISIS pulsed neutron source. Issue 11 (24th February 2016) - Telling, Mark T. F.; Campbell, Stuart I.; Engberg, Dennis; Martín y Marero, David; Andersen, Ken H.
Abstract : Correction for 'Spectroscopic characteristics of the OSIRIS near-backscattering crystal analyser spectrometer on the ISIS pulsed neutron source' by Mark T. F. Telling et al., Phys. Chem. Chem. Phys., 2005, 7, 1255–1261.